2013
DOI: 10.1007/s11926-013-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity on Function and Quality of Life in Chronic Pain Conditions

Abstract: Many people throughout the world have both chronic pain and obesity. Overweight and obese people are more prone to a proinflammatory state manifesting as metabolic syndrome but also to a higher prevalence of chronic pain comorbidities. Obesity and a high body mass index (BMI) are associated with impaired functional capacity and reduced quality of life (QoL) in patients with chronic pain conditions. Systemic inflammation is not only involved in metabolic syndrome but it also initiates and perpetuates chronic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 93 publications
2
70
0
5
Order By: Relevance
“…The discounting of women's pain may put women who are both undertreated for chronic pain and who are overweight or obese at risk for greater disability and reduced quality of life. 2 These risks are in addition to the stigmatization and negative social consequences (e.g., lower occupational and educational attainment) of being overweight or obese. 13,14,21,26,52,57,63 Additionally, obese women may have less social support to buffer against these disadvantages, as obesity is linked to less social contact and greater loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…The discounting of women's pain may put women who are both undertreated for chronic pain and who are overweight or obese at risk for greater disability and reduced quality of life. 2 These risks are in addition to the stigmatization and negative social consequences (e.g., lower occupational and educational attainment) of being overweight or obese. 13,14,21,26,52,57,63 Additionally, obese women may have less social support to buffer against these disadvantages, as obesity is linked to less social contact and greater loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based studies of obesity and chronic pain are restricted to specific specialties such as rheumatology [18][19][20][21] or to specific conditions such as arthritis 22-24 and low-back pain. Only a limited number of articles on this topic have been published in pain medicine literature.…”
mentioning
confidence: 99%
“…Studies have shown that chronic pain affects approximately 25-35% of adults worldwide depending on the definition used [11]. In the United States an estimated prevalence of 30% has been reported with more females than males affected [12] and worldwide the prevalence is estimated to be over 20% of all adults, with 10% newly diagnosed each year [13,14].…”
Section: Chronic Musculoskeletal Pain and Obesitymentioning
confidence: 99%
“…These biomarkers sensitise nociceptors lowering their thresholds of activation resulting in an amplified nociceptive input to the central nervous system. Hence, adiposopathy may contribute to non-resolving systemic inflammation and states of persistent pain [1,12,34,43]. Furthermore, unresolving systemic inflammation may contribute to continued sensitisation of the nociceptive system and may also prevent the healing of tissue in the periphery [44].…”
Section: Chronic Musculoskeletal Pain and Obesitymentioning
confidence: 99%